Mitochondrial sequence‐based evolutionary analysis of riverine–swamp hybrid buffaloes of India indicates novel maternal differentiation and domestication patterns. (12th April 2020) - Singh, R.; Lava Kumar, S.; Mishra, S. K.; Gurao, A.; Niranjan, S. K.; Vohra, V.; Dash, S. K.; Rajesh, C.; Kataria, R. S.
Summary: In this study, mitochondrial D‐loop sequence data on riverine, swamp and hybrid buffaloes from India have been generated and compared with other reported Indian riverine, Chinese and Bangladeshi swamp buffalo populations. Sequence analysis revealed the presence of 132 haplotypes, with a haplotype diversity of 0.9611 ± 0.0045 and a nucleotide diversity of 0.04801 ± 0.00126. For the first time, the existence of riverine–swamp hybrids among the Indian Chilika buffalo population has been recorded, having 49 chromosomes, which was also confirmed by mitochondrial haplotype sharing between Chilika and Indian swamp as well as Chinese swamp buffalo populations in the network analysis. Phylogenetic analysis documents the sharing of reported pre‐domestication haplogroups 'SA1', 'SA2', 'SA3' and 'SB1' between the Chilika and swamp buffalo populations of India, China and Bangladesh, an indication of the migration of swamp buffaloes towards Bangladesh and adjoining lower parts of India and north towards Chinese domestication sites. The results have also been supplemented by multidimension scaling, grouping Indian and Chinese swamp buffaloes more closely together with Bangladeshi buffaloes, but into a separate quadrant, whereas Chilika grouped away from other riverine as well as swamp buffaloes. These findings thus confirm the previous reports that the northeast region of India, close to the Indo‐China border, is the point of evolution of swamp buffaloes with multiple sites of domestication.